Cassandra’s Madness in Aeschylus’ Agamemnon - (:unkn) unknown (My University, 2023)
Cassandra’s prophetic capacity is presented by Aeschylus as a disease, bringing suffering associated with pain and death, in language found also in the Hippocratic corpus, in particular De morbo sacro.
Keywords: Humanidades::Lenguas y Literatura